2006
DOI: 10.3402/ijch.v65i5.18132
|View full text |Cite
|
Sign up to set email alerts
|

Food security in Nunavut, Canada: barriers and recommendations.

Abstract: Objectives. The food supply of Inuit living in Nunavut, Canada, is characterized by market food of relatively low nutritional value and nutrient-dense traditional food. The objective of this study is to assess community perceptions about the availability and accessibility of traditional and market foods in Nunavut. Study Design. A qualitative study using focus group methodology. Methods. Focus groups were conducted in 6 communities in Nunavut in 2004 and collected information was analyzed. Results. Barriers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
185
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(198 citation statements)
references
References 26 publications
10
185
0
3
Order By: Relevance
“…Food security research in the Canadian Arctic appears to be expanding (37)(38)(39) , with many recent publications from the International Polar Year Inuit Health Survey (1,4,34,35) and other food security studies (40)(41)(42) , while research with on-reserve FN populations is lacking (2) and only beginning to be conducted and reported. Collecting data with isolated communities is not without merit as each reserve has unique characteristics and many want local information to direct local policies and programmes (43)(44)(45) .…”
Section: Discussionmentioning
confidence: 99%
“…Food security research in the Canadian Arctic appears to be expanding (37)(38)(39) , with many recent publications from the International Polar Year Inuit Health Survey (1,4,34,35) and other food security studies (40)(41)(42) , while research with on-reserve FN populations is lacking (2) and only beginning to be conducted and reported. Collecting data with isolated communities is not without merit as each reserve has unique characteristics and many want local information to direct local policies and programmes (43)(44)(45) .…”
Section: Discussionmentioning
confidence: 99%
“…dietary fibre, folate, potassium, vitamins A, B6, and D), leading to a double burden of under-nutrition and over-nutrition (46,63,(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78) . Moreover, food security presents a growing issue, particularly for traditional foods, as climate change alters the physical landscape and poverty rates among the Aboriginal populations remain high (46,(79)(80)(81)(82)(83)(84)(85)(86)(87)(88) . The rapid lifestyle and nutrition transition may explain the rising prevalence of chronic diseases and higher rates of mortality among aboriginal populations in Canada compared to the general population (89)(90)(91)(92)(93) .…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%
“…Previous studies in Eeyouch found higher intakes of TF to be associated with older age, walking more than 30 min a day, and having fewer years of schooling [19]. Likely obstacles to Eeyouch procuring TF based on data from other Indigenous groups include lack of transmission of traditional knowledge of hunting and preserving TF; the time, cost and energy required for harvesting activities; the yearly and seasonal availability of game and fish; climate change; and wage labour opportunities [21,23–25]. …”
Section: Introductionmentioning
confidence: 99%